1967
DOI: 10.1113/jphysiol.1967.sp008348
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit types of cat triceps surae muscle

Abstract: SUMMARY1. Motor units, defined as including a motoneurone (cell body, dendrites and axon) plus the muscle unit innervated, have been examined in the triceps surae motor pool of pentobarbital anaesthetized cats.2. The technique of intracellular stimulation and recording which was used permitted measurement of the axonal conduction velocity, post-spike hyperpolarization duration and input resistance of individual motoneurones, and the correlation of these properties with the characteristics of the twitch and tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
171
2
2

Year Published

1968
1968
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 333 publications
(193 citation statements)
references
References 29 publications
18
171
2
2
Order By: Relevance
“…Recent control experiments have shown considerable diminution of twitch tension, plus variable but relatively small changes in twitch time to peak, in type F units studied both before and after tetanic MG contraction with the muscle unloaded. The distribution of motor unit twitch characteristics obtained in further control experiments in which the muscles were never allowed to shorten without load has been similar to that reported in the first paper of this series (Burke, 1967a), with the addition of a few type F units with twitch tension output of less than 1-5 g. Thus it can be concluded that the twitch tension values recorded for many units in the present investigation were in all likelihood abnormally low, and that in addition the distinction between fast and slow twitch units may have been somewhat blurred, so that the twitch characteristics of the motor units in the present sample may match those of the earlier sample much more closely than I had appreciated at first. With this reservation, the conclusions drawn from the present investigation stand essentially umnodified.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Recent control experiments have shown considerable diminution of twitch tension, plus variable but relatively small changes in twitch time to peak, in type F units studied both before and after tetanic MG contraction with the muscle unloaded. The distribution of motor unit twitch characteristics obtained in further control experiments in which the muscles were never allowed to shorten without load has been similar to that reported in the first paper of this series (Burke, 1967a), with the addition of a few type F units with twitch tension output of less than 1-5 g. Thus it can be concluded that the twitch tension values recorded for many units in the present investigation were in all likelihood abnormally low, and that in addition the distinction between fast and slow twitch units may have been somewhat blurred, so that the twitch characteristics of the motor units in the present sample may match those of the earlier sample much more closely than I had appreciated at first. With this reservation, the conclusions drawn from the present investigation stand essentially umnodified.…”
Section: Discussionsupporting
confidence: 81%
“…Given other, more intense stimulation, the larger tension type F units undoubtedly participate but such states could not be tested because of the technical limitations of the intracellular approach. As has been found true of soleus motor units (Denny-Brown, 1929;Granit, 1958), the maximum firing frequencies of both type S and type F* units during muscle stretch, although different from one another (see Table 1), were in each case lower than that required for complete fusion of tetanic tension of the individual muscle units (Burke, 1967a, see also Kernell, 1966b). However, the summated tension profile of the whole muscle can remain relatively smooth because of the small individual unit tension outputs (see Fig.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations